2015
DOI: 10.1089/ten.tec.2014.0709
|View full text |Cite
|
Sign up to set email alerts
|

Automation of Pressure Control Improves Whole Porcine Heart Decellularization

Abstract: Whole heart decellularization combined with patient-specific cells may prove to be an extremely valuable approach to engineer new hearts. Mild detergents are commonly used in the decellularization process, but are known to denature and solubilize key proteins and growth factors and can therefore be destructive to the extracellular matrix (ECM) during the decellularization process. In this study, the decellularization of porcine hearts was accomplished in 24 h with only 6 h of sodium dodecyl sulfate exposure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 47 publications
2
29
0
1
Order By: Relevance
“…6,25,26 As stated by Taylor et al 27 as one of the pioneers in developing whole organ decellularization, the improvement of the decellularization process to produce ECM from deceased organs is one of the most notable achievements in the field of tissue engineering within the past 7 years. Acellular ECM can be obtained by decellularization of native tissue either by perfusing detergent solutions through the vasculature or diffusion of this solution through pieces of tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,25,26 As stated by Taylor et al 27 as one of the pioneers in developing whole organ decellularization, the improvement of the decellularization process to produce ECM from deceased organs is one of the most notable achievements in the field of tissue engineering within the past 7 years. Acellular ECM can be obtained by decellularization of native tissue either by perfusing detergent solutions through the vasculature or diffusion of this solution through pieces of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain cECM, the hearts were decellularized in an automated pressure and temperature-controlled apparatus designed and built by our group as described previously. 6 In the SDS group, hearts were rinsed by antegrade perfusion with 1X PBS and type 1 distilled water (DW) for 1 h each, followed by three sets of 0.5% (w/v) SDS solutions for 2 h each with 1 h of nonrecycled DW between each set. In the Triton X-100 (TX-100, fisher Scientific, fair Lawn, Nj) group, hearts were perfused with 1× PBS, and type 1 DW for 1 h each, followed by three sets of 0.5% SDS solutions for 2 h each with 1 h of nonrecycled DW between each set.…”
Section: Harvesting and Decellularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of this topic is limited. It has been shown that automating pressure during decellularization with digital pressure sensors improves whole heart decellularization [23], however the effects of pressures have not been studied despite the variations in pressure between protocols. The same holds true for total decellularization time.…”
Section: Introductionmentioning
confidence: 99%